National Survey of Pediatric Intestinal Rehabilitation Programs in the United States. Issue 6 (3rd September 2020) - Park, Christine J.; Shaughnessy, Matthew P.; Zhang, Lucy; Armenia, Sarah J.; Caty, Michael G.; Cowles, Robert A.
Abstract: Background: Pediatric intestinal rehabilitation (PIR) programs are associated with improved outcomes in children with intestinal failure but remain heterogeneous nationally. This study characterizes PIR program components to aid those seeking to establish or expand a program. Methods: Members of the Children's Hospital Association reporting a PIR program to the US News and World Report completed a 14‐item questionnaire using the Qualtrics Online Survey Software. Programs were categorized as small or large (≤50 vs >50 patients) and new or established (≤10 vs >10 years). Results: Seventy‐one programs were identified and 61 surveys were returned for a response rate of 86%. Majority of programs had gastroenterology, surgery, nutrition, nursing, and social work services involved. Large programs (n = 34; 59%) were more likely to serve as referral centers; have greater participation by nursing, social work, and primary care; have more dedicated time by gastroenterology, surgery, nursing, nutrition, and social work; have more frequent meetings; and have various funding sources ( P < .05). Conclusion: Critical components of a PIR program include gastroenterology, surgery, and nutrition services with strong nursing and social work support. These data document the components of modern PIR programs, though further studies on the relationship between program structure and patient outcomes are warranted.